COOPERATIVE LEARNING FOR ENHANCED READING COMPREHENSION: A STUDY WITH FIRST-YEAR STUDENTS - Mustamir, Mustamir; Jauhar, Sitti; Sudarto, Sudarto; Rachman, Sidrah Afriani (University of Kuningan, 2023)
This research aimed to determine the effectiveness of teaching reading comprehension using a cooperative learning model for first-year students at Universitas Muhammadiyah Bone. The study employed a quasi-experimental design, involving two groups: an experimental group (30 students) and a control group (30 students). Both groups underwent pre-test assessments, material presentations, and post-test evaluations. The data, collected through multiple-choice items, were analyzed using mean scores and the t-test formula. The research revealed that reading comprehension improved significantly in the experimental group (mean score 83.11) compared to the control group (mean score 61.56). The t-test also indicated a significant difference between the two groups, favoring the cooperative learning model. In conclusion, the use of the cooperative learning model effectively enhances students' reading comprehension.